A systematic review of how endocrine-disrupting contaminants are sampled in environmental compartments: wildlife impacts are overshadowed by environmental surveillance - Angela Simms; Kylie Robert; Ricky-John Spencer; Sarah Treby; Kelly Williams-Kelly; Candice Sexton; Rebecca Korossy-Horwood; Regan Terry; Abigail Parker; James Van Dyke (Environmental Science and Pollution Research, 2025)
Endocrine-disrupting contaminants (EDCs) are frequently monitored in environments because of their biological impacts on wildlife and humans. We conducted a systematic review using Web of Science to identify global research trends for EDC environmental sampling. Specifically, we aim to better understand geographic variation in (1) the compartment that EDCs were sampled in the environment; (2) the types of EDC sampled; and (3) the taxa that are sampled. A total of 9140 papers were found, of which 2554 were included in our review. The number of studies sampling EDCs varied between continents, with majority of research occurring in Europe, Asia, and North America. Although economy and access to technology will contribute to the number of articles published, we found the current output of research showed distinct disparities in sampling methods. Across all continents, water was the most frequently sampled compartment to determine EDC concentrations (sampled in 50–75% of studies). Wildlife was sampled far less often in studies across all continents, comprising 30% of studies at most. Pharmaceuticals were the most commonly studied chemical group, and fish were the most commonly sampled taxonomic group. Although far fewer studies sampled for EDCs in wildlife compared with abiotic compartments, these studies provide valuable information on the potential consequences of environmental EDC exposure and link environmental surveillance of EDCs with lab-measured organism-level effects. Studies that sampled only the water matrix for EDCs may be doing so as a proxy despite the large knowledge gaps on how environmental EDCs affect wildlife at varying concentrations.